Crisis Management of PT. Nindya Karya (Persero) Based on Organizational Culture and Leadership - Hidayat, Taufik; Wahyuni, Sari (Eduvest - Journal of Universal Studies, 2025)
The Covid-19 pandemic has evolved into a global crisis that extends beyond the health sector, significantly impacting various aspects of society, including the construction industry. This study employs a qualitative method using a phenomenological approach to explore how organizational actors perceive and respond to the crisis. The concept of intentionality is used to understand individual consciousness and lived experiences during the pandemic. The findings reveal that organizational culture plays a pivotal role in ensuring the continuity of operations throughout all phases of crisis management. Core institutional values, shared knowledge, and habitual organizational practices serve as internal strengths that enable effective adaptation. An adaptive organizational culture enhances resilience and readiness in the face of unexpected disruptions. Additionally, leadership emerges as a key determinant in shaping the organization’s response to crisis situations. The study highlights that adaptive leadership characterized by flexibility, decisiveness, and emotional intelligence is essential for navigating uncertainties. The implications of this research suggest that both adaptive culture and leadership competencies must be actively developed to strengthen organizational crisis preparedness, particularly in high-risk sectors such as construction. These findings provide practical insights for policymakers and organizational leaders aiming to build more resilient and responsive institutions in the post-pandemic era.